The Effect of Good University Governance on Financial Management Performance with Organizational Culture as an Intervening Variable at Sriwijaya Buddhist State College - Andhyka Wicaksono; Pringgondani Pringgondani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research uses organizational culture as an intervening variable at STABN Sriwijaya in order to examine the impact of good university governance (GUG) on financial management performance. The Sobel test and path analysis approaches are used in this quantitative research. The hypothesis is stated as follows: (a) H1 = GUG has a positive and significant impact on STABN Sriwijaya's financial management performance; (b) H2 = GUG has a positive and significant impact on STABN Sriwijaya's organizational culture; (c) H3 = Organizational culture has a positive and significant impact on STABN Sriwijaya's financial management performance; and (d) H4 = GUG has a positive and significant impact on STABN Sriwijaya's financial management performance through Organizational Culture. According to the research's findings, the Sobel test indicates that GUG has a positive and significant impact on financial management performance through organizational culture as an intervening variable. The computed z value of 4.78 is bigger than the z table value of 1.96. Meanwhile, from the path analysis, it can be seen that the coefficient value of GUG direct influence on Financial Management Performance is 0.336, and the coefficient value of GUG indirect influence on Financial Management Performance is 0.375. Because the direct relationship coefficient is smaller than the indirect relationship coefficient (0.336<0.375), it can be said that the relationship between GUG and Financial Management Performance is an indirect relationship because it is influenced by Organizational Culture as an intervening variable.